150 The effect of competition for an automated supplement feeder on supplement intake behavior of stocker steers - Husz, Taylor C (J Anim Sci, 2020)
The objective of this research was to determine the effect of competition for a feeding space at an automated supplement feeder on supplement intake behavior. A 2 yr study was conducted; each yr, 128 mixed-breed beef steers (n = 256, initial BW = 245 ± 27.5 kg) were randomly assigned to 8 paddocks. One paddock each yr (n = 16 steers) was selected to have continuous access to the feeder for the duration of the 16 wk trial; this paddock was designated the “tester” paddock. The automated feeder had 4 feeding stations that dispensed supplement after eligible animal’s RFID tags were read by the electronics of the feeder. Steers were limited to 0.50 kg supplement/d. Weekly, additional paddocks were commingled with the tester paddock to increase competition for the feeder. This resulted in a stocking density from 4 to 32 steers per feeding station. For yr 2, one feeding station was disabled, resulting in a stocking density of 5.3 to 42.7 steers per feeding station. Approximately 31% of the steers did not voluntarily use the feeder; therefore, effective competition was less than the study design. Mean weekly supplement intake and GPS location were recorded for steers in the tester paddock. Additionally, pedometer data were collected in yr 2. Weekly mean supplement intake and time spent near the feeder were regressed on actual feeder stocking density with yr as a random variable; wk was the experimental unit (n = 16 wk). Tester steers consumed an average of 0.27 kg supplement/d. Competition for a feeding station numerically reduced (P = 0.01) supplement intake by 5 g/d per steer of additional competition. Steers spent 4.4% of the time within 15 m of the feeder regardless of competition (P = 0.54). As competition increased, steers took more steps (P < 0.01). These data illustrate that in environments similar to this experiment, the feeder can be stocked with at least 20 animals per feeding station with minimal effects on supplement intake.